PERLINDUNGAN HUKUM TERHADAP SAKSI PELAPOR DALAM TINDAK PIDANA NARKOTIKA (Studi Penelitian Di Polres Langkat) - Zuran, M Adhit; Sumiadi, Sumiadi; Subaidi, Joelman (Fakultas Hukum Universitas Malikussaleh, 2024)
Narcotics abuse in Indonesia has reached a very worrying level. Narcotics abuse is regulated in the Republic of Indonesia Law Number 35 of 2009 concerning Narcotics. The role of law enforcement officers and community participation is needed in preventing and eradicating narcotics abuse. Witness and victim protection aims to provide a sense of security so that they can provide information honestly and openly. Currently, witnesses and reporters of narcotics crimes still lack legal protection, making them vulnerable to threats and terror. Discussions regarding legal protection for reporting witnesses and obstacles in its implementation are the main focus. The research method used is an empirical juridical research method, with a descriptive research nature that focuses on field studies. The data used are primary and secondary data. The research results show that legal protection for reporting witnesses includes maintaining identity confidentiality and providing security protection for reporting witnesses from physical threats so that reporting witnesses feel safe in providing information that they know about a narcotics crime that has occurred or is currently occurring. The obstacles in carrying out legal protection are because there is still fear from reporting witnesses and also a feeling of ignorance from the public about criminal acts that occur around them, which becomes an obstacle for the police in providing protection. Efforts to increase legal protection for witnesses and victims by the authorities require improvements in the systems, services and procedures that have been regulated within the witness and victim protection framework. It is recommended that the police need to increase awareness of protection for reporting witnesses. It is important to socialize the role of witnesses in uncovering narcotics crimes. With more effective outreach, it is hoped that the public will be braver and more active in utilizing the protection services provided by these two institutions, increasing their trust and participation.